Legal Rationale of Biodiversity Regulation as a Basis of Stable Ecological Policy - ZAKHARCHENKO, Natalya V.; HASANOV, Seymur L.; YUMASHEV, Alexey V.; ADMAKIN, Oleg I.; LINTSER, Svetlana A.; ANTIPINA, Marina I. (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018DO - 10.14505//jemt.v9.3(27).11, 2018)
The paper understands cross-border natural resources as a totality of characteristics of local ecological systems, which can act as regulators of human’s life space. Authors state that uniqueness of this phenomenon is defined by the fact that all natural resources act as a single system of planet scale. The problem distinguished in the paper is based on the fact that in the period of ecological systems and natural resources development a little attention is paid to cross-border management on the part of nations they belong to. The research subject is an indicator of stability and quality of management of cross-border natural resources in the aspect of their even existing and carrying out of their functions. Scientific novelty of the research is that it’s proved for the first time that each ecological system has s number of parameters, one of which shows how much it resistant to human impact. The system of providing biodiversity is one of such parameters. In the paper the legal characteristics of the issue are identified with the actual state of interstate cooperation and the opportunity of its expansion within the already existing interstate formation is determined. The example of such formation is European Union. The areas of further research can be defined as an expansion of specified cooperation of Asian and South American continent.